Targeting the gut-liver axis in cholangiocarcinoma: mechanisms, therapeutic advances, and future directions - Wang, Lu; Qiao, Weiwei; Zhen, Xiaowen; Zhang, Yeqiong; Dong, Zhiwei (Frontiers in Oncology, 2025)
Cholangiocarcinoma (CCA), a highly aggressive biliary tract malignancy, exhibits rising incidence rates and an extremely poor prognosis. Recent studies reveal that gut-liver axis dysregulation drives CCA progression through gut microbiota dysbiosis, bile acid (BA) metabolic disturbances, and immune microenvironment remodeling. Clinical evidence highlights significant alterations in the gut and biliary microbial composition of CCA patients, which correlate with tumor stage, vascular invasion, and survival outcomes. Dysregulated BA metabolism in CCA, characterized by accumulation of primary conjugated BAs, promotes tumor invasiveness via interaction with specific BA receptors and fosters an immunosuppressive microenvironment. Emerging therapeutic strategies include antibiotics for pathogenic microbiota modulation, probiotics for microbial homeostasis restoration, fecal microbiota transplantation, and BA pathway modulators. Future directions necessitate integrating synthetic biology (engineered microbiota), multi-omics, and artificial intelligence to develop precision therapies. Targeting the gut-liver axis offers novel therapeutic perspectives for CCA; however, clinical translation demands deeper mechanistic insights and standardized protocols to address challenges such as microbiota heterogeneity and receptor signaling duality.